(untitled) (Bangladesh Journal of Medical Physics, 2025)
The aim of this study is a comprehensive investigation of measurement stability of MARS spectral computed tomography to evaluate the variability in the measured spectral signature of different materials and count rate capability of Medipix3RX chip. The intra and inter-scan measurement variation of the mass attenuation coefficient of different materials and the count rate capability of the Medipix3RX chip were evaluated. A repeated scan was performed using multi-contrast phantom in different MARS scanner to quantify the error of the mass attenuation coefficient of different materials. A hypothesis was made to assume how different instabilities occurred measurement variation in the spectral signature. The performance of a relative count rate of different charge summing counter was also evaluated to investigate the temporal stability of the Medipix3RX photon-counting detector. The mass attenuation profile of different composite and single materials produces scan variation in repeated measurement. The variation of the mass attenuation coefficient of composite materials was significantly higher compared to the single materials. The Bland-Altman plot shows that the linear attenuation coefficients of each voxel corresponding to each composite material produce more outlier points outside the 95% confidence interval than single materials. Relative count variation in each charge summing counter of Medipix3RX chip was observed during repeated air scan. These investigations provide useful insights into the source of variation of the MARS spectral CT system and indicate potential areas where future improvements in performance may be made. Ban. J. Med. Phys., Vol -16, Issue -2, 2025 : 44-55